Perumusan Model Penyelesaian Sengketa Tanah yang Adil: Pendekatan Dekonstruksi Derrida terhadap Kasus Eks Konsesi Dumai - Husendro Husendro (Jurnal Penelitian Hukum De Jure, 2025)
Dumai City is an area with land concession permits for oil and gas companies, including PT. Chevron Pacific Indonesia. These extensive and long-term land concession permits often conflict with local (indigenous) communities, urban development, and population growth. Although the company’s concession period has expired and the land must be returned to the government, land claims, disputes, and conflicts remain unresolved. Therefore, a just, holistic, and human rights-based resolution will be a fundamental element of this resolution. The research method used is a normative empirical one with data sources obtained from field observations and interviews with various stakeholders, including the government and local communities. This paper will focus on how Jacques Derrida’s concept deconstructs the settlement of the former Dumai concession case by dissecting the dominant legal narrative that supports ownership, concession claims, revealing the contradictions and power structures inherent in the land tenure system. This paper proposes alternative dispute resolution models, such as conciliation, based on different principles, future justice, and openness to plural legal subjects. Through Derrida’s deconstruction and conciliation efforts, various alternative justice-based concession land solutions will be formulated for corporations (PT. CPI), local (indigenous) communities, citizens, local governments, vertical agencies, business actors, including law enforcement options.